Long-term safety and efficacy of tezacaftor–ivacaftor in individuals with cystic fibrosis aged 12 years or older who are homozygous or heterozygous for Phe508del CFTR (EXTEND): an open-label extension study. Issue 7 (July 2021) - Flume, Patrick A; Biner, Reta Fischer; Downey, Damian G; Brown, Cynthia; Jain, Manu; Fischer, Rainald; De Boeck, Kris; Sawicki, Gregory S; Chang, Philip; Paz-Diaz, Hildegarde; Rubin, Jaime L; Yang, Yoojung; et al.
Summary: Background: Tezacaftor–ivacaftor is an approved cystic fibrosis transmembrane conductance regulator (CFTR) modulator shown to be efficacious and generally safe and well tolerated over 8–24 weeks in phase 3 clinical studies in participants aged 12 years or older with cystic fibrosis homozygous for the Phe508del CFTR mutation (F/F; study 661-106 [EVOLVE]) or heterozygous for the Phe508del CFTR mutation and a residual function mutation (F/RF; study 661-108 [EXPAND]). Longer-term (>24 weeks) safety and efficacy of tezacaftor–ivacaftor has not been assessed in clinical studies. Here, we present results of study 661-110 (EXTEND), a 96-week open-label extension study that assessed long-term safety, tolerability, and efficacy of tezacaftor–ivacaftor in participants aged 12 years or older with cystic fibrosis who were homozygous or heterozygous for the Phe508del CFTR mutation. Methods: Study 661-110 was a 96-week, phase 3, multicentre, open-label study at 170 clinical research sites in Australia, Europe, Israel, and North America. Participants were aged 12 years or older, had cystic fibrosis, were homozygous or heterozygous for Phe508del CFTR, and completed one of six parent studies of tezacaftor–ivacaftor: studies 661-103, 661-106, 661-107, 661-108, 661-109, and 661-111. Participants received oral tezacaftor 100 mg once daily and oral ivacaftor 150 mg once every 12 h for up to 96 weeks. The primary endpoint was safety and tolerability. Secondary endpoints were changes in lung function, nutritional parameters, and respiratory symptom scores; pulmonary exacerbations; and pharmacokinetic parameters. A post-hoc analysis assessed the rate of lung function decline in F/F participants who received up to 120 weeks of tezacaftor–ivacaftor in studies 661-106 (F/F) and/or 661-110 compared with a matched cohort of CFTR modulator-untreated historical F/F controls from the Cystic Fibrosis Foundation Patient Registry. Primary safety analyses were done in all participants from all six parent studies who received at least one dose of study drug during this study. This study was registered at ClinicalTrials.gov (NCT02565914 ). Findings: Between Aug 31, 2015, to May 31, 2019, 1044 participants were enrolled in study 661-110 from the six parent studies of whom 1042 participants received at least one dose of study drug and were included in the safety set. 995 (95%) participants had at least one TEAE; 22 (2%) had TEAEs leading to discontinuation; and 351 (34%) had serious TEAEs. No deaths occurred during the treatment-emergent period; after the treatment-emergent period, two deaths occurred, which were both deemed unrelated to study drug. F/F (106/110; n=459) and F/RF (108/110; n=226) participants beginning tezacaftor–ivacaftor in study 661-110 had improvements in efficacy endpoints consistent with parent studies; improvements in lung function and nutritional parameters and reductions in pulmonary exacerbations observed in the tezacaftor–ivacaftor groups in the parent studies were generally maintained in study 661-110 for an additional 96 weeks. Pharmacokinetic parameters were also similar to those in the parent studies. The annualised rate of lung function decline was 61·5% (95% CI 35·8 to 86·1) lower in tezacaftor–ivacaftor-treated F/F participants versus untreated matched historical controls. Interpretation: Tezacaftor–ivacaftor was generally safe, well tolerated, and efficacious for up to 120 weeks, and the safety profile of tezacaftor–ivacaftor in study 661-110 was consistent with cystic fibrosis manifestations and with the safety profiles of the parent studies. The rate of lung function decline was significantly reduced in F/F participants, consistent with cystic fibrosis disease modification. Our results support the clinical benefit of long-term tezacaftor–ivacaftor treatment for people aged 12 years or older with cystic fibrosis with F/F or F/RF genotypes. Funding: Vertex Pharmaceuticals Incorporated.